Online Marketing vs Direct Selling, Siapa yang Unggul? - Ayu, Adinda (Wacana Equiliberium (Jurnal Pemikiran Penelitian Ekonomi), 2020)
The rapid development of technology has an effect on buying and selling activities. In addition to directly visiting the store we can carry out buying and selling transactions at home only with intermediaries gadget and internet. There are advantages and disadvantages of each of these transactions. Not a few buyers and sellers are made losses because they are not careful in making transactions whether it is online or offline. The purpose of this article is for readers to know the strengths and weaknesses of each method of transaction so that they do not have to meet with losses while making transactions. Helping to make sure when to do transactions online or offline is also one of the goals so that it gets efficiency in buying and selling transactions.